LASER BIOPHOTONICS : Laser speckle contrast imaging of cerebral autoregulation in rats at a macro- and microcirculation level. (30th June 2016) - Semyachkina-Glushkovskaya, O V; Abdurashitov, A S; Sindeev, S S; Tuchin, V V
Abstract: Using the method of laser speckle imaging for the simultaneous study of macro- and microcirculation in cerebral vessels of healthy rats, we show that the mechanisms underlying cerebral autoregulation depend on the initial condition of the organism and the sex of individual animals. The pharmacological dose-dependent stimulation of the peripheral arterial pressure increase is not accompanied by the cerebral circulation responses of analogous intensity, but manifests itself as 'compensating' reactions, namely, the redistribution of the blood flow at the level of macro- (in females) and microcirculation (in females and males). The obtained results extend our understanding of the capabilities of laser speckle imaging technique in neurophysiological studies of reserve abilities of cerebral circulation autoregulation under the conditions of hypertensive status formation.